Assessment on the incidence of aflatoxin B1 in composite cattle feed and raw materials in India - R. Murugeswari (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Composite cattle feed samples and raw materials like maize, wheat, sorghum, broken rice, pearl millet, groundnut cake, cotton seed cake, mustard cake, soyabean meal, rapeseed meal, sunflower meal, guar meal, safflower meal, deoiled rice bran and wheat bran were collected from various parts of India for a period 5 years and evaluated for aflatoxin B1 level by screening through ELISA and confirmation through HPLC. Among the 482 composite cattle feed samples, only 68.5per cent were having aflatoxin Bilevel below the permissible level (below 20 ppb). Higher incidence of aflatoxin B1 was recorded in west zone than east, north and south zones during monsoon period. However, it was observed that incidence of aflatoxin B1 at concentration beyond 100ppb was relatively higher in eastern zone both during monsoon and non-monsoon period than the west, north and south zones. Among the energy source, maize had the highest (7.8 per cent, 15 out of 193 samples tested) prevalence of alarming levels of aflatoxin (>100ppb) and 41.5 per cent (80 samples) in the range of 21 to 100 ppb of aflatoxin B1. Only 50.8 per cent (98 samples) were within permissible level (